Perbedaan Kadar Asam Urat Pada Seseorang Dengan Hipertensi Dan Non Hipertensi Di Kecamatan Jebres Kota Surakarta - Nurudhiya, Olivia; , dr. Sigit Widyatmoko Sp.PD; , dr. Safari Wahyu Jatmiko (2016)
Backgrounds : Hypertension is the number of agreements based on clinical evidence, consensus, and epidemiological studies of the meta-analysis, which is an increase of blood pressure above or equal to 140/90 mmHg. Uric acid is the end product of purine metabolism. Hypertension can lead to increased levels of uric acid in the blood. Increased levels of uric acid in the blood causes a decrease in renal perfusion, thus stimulating the reabsorption of uric acid and the end result is an increase in levels of uric acid in the blood. Purpose : The purpose of the research is to know the differences in levels of uric acid in a person with hypertensive and non-hypertensive in District Jebres Surakarta city Method : This research is a cross sectional analytic, puskesmas election made after conducting a preliminary study on the data the incidence of hypertensive patients in Surakarta followed by sampling using consecutive sampling. Data obtained from the measurement directly on the sample. Results : Statistical analysis was performed with Fisher test p value = 0.00, the value of RP = 3.4, and the value of CI is 2.4 to 4.8, which means there are significant differences uric acid levels in a person with hypertensive and non-hypertensive. Conclusions : There is a significant difference in levels of uric acid in a person with hypertensive and non-hypertensive in District Jebres, Surakarta city Keywords : : Hypertension, uric acid levels